2011
DOI: 10.1016/j.etap.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Serum unconjugated bisphenol A concentrations in men may influence embryo quality indicators during in vitro fertilization

Abstract: Here we assess bisphenol A (BPA) in couples undergoing in vitro fertilization (IVF) and indicators of embryo quality; embryo cell number (ECN) and embryo fragmentation score (EFS). Twenty-seven couples provided serum on the day of oocyte retrieval. Unconjugated BPA was measured by HPLC with Coularray detection. Odds ratios (OR) were generated using ordinal logistic regression including female and male BPA concentrations, age and race, and day of embryo transfer for ECN. Inverse associations are suggested for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…Findings from these studies indicate that infertile women have higher serum BPA levels compared to fertile women (17, 18). Further, studies conducted in women undergoing in vitro fertilization (IVF) treatments show that BPA levels (total or unconjugated BPA) were inversely associated with peak estradiol levels, number of oocytes retrieved, oocyte maturation, fertilization rates, and embryo quality (1923). Thus, increased levels of BPA may decrease the success rate of IVF treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from these studies indicate that infertile women have higher serum BPA levels compared to fertile women (17, 18). Further, studies conducted in women undergoing in vitro fertilization (IVF) treatments show that BPA levels (total or unconjugated BPA) were inversely associated with peak estradiol levels, number of oocytes retrieved, oocyte maturation, fertilization rates, and embryo quality (1923). Thus, increased levels of BPA may decrease the success rate of IVF treatments.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have documented that exposure to drugs affects sperm DNA methylation marks, which are transmitted to progeny, leading to abnormal embryo development, developmental errors, and transgenerational ef-fects. Recently, Bloom et al [36] showed an inverse association between male serum BPA concentrations and embryo quality during in vitro fertilization, suggesting an effect of male BPA exposure on sperm quality, thereby affecting the embryo development. Recently, Bloom et al [36] showed an inverse association between male serum BPA concentrations and embryo quality during in vitro fertilization, suggesting an effect of male BPA exposure on sperm quality, thereby affecting the embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…5D). [218][219][220][221][222]267 Thus, collectively, these studies suggest that low dose BPA exposure exerts adverse effects on growing follicles in the adult ovary.…”
Section: Integration Of Endpoints Across Levels Of Biological Organizmentioning
confidence: 95%